Online social support for Complex Regional Pain Syndrome: a content analysis of support exchanges within a newly launched discussion forum - Smedley, Richard M.; Coulson, Neil S.; Gavin, Jeff; Rodham, Karen; Watts, Leon (Elsevier, 2015)
Complex Regional Pain Syndrome is a debilitating illness characterised by unexplained pain that is disproportionate to any initiating event. Individuals living with CRPS can become socially isolated, and online support communities may provide them with an increased support network through which they can access support at any time. However, most research into online social support has focussed on established communities rather than newly launched communities, and little is known about online support for CRPS. This study explores the experiences of members in a newly launched CRPS discussion forum, to examine the support content of messages and how support processes become established. Content analysis was used to code messages using the Social Support Behavior Code. Emotional support was the most common, followed by informational, esteem and network support, with tangible aid occurring only rarely. Support processes started almost immediately when the group was launched, similar to what happens in a face-to-face support group where strangers meet for the first time and immediately support one another. The results support Optimal Matching Theory, and indicate that online support may have an important role to play in the CRPS ‘four pillars of intervention’